At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
First, let's analyze the given functions:
The function is:
[tex]\[ f(x) = \frac{1}{3}x - 2 \][/tex]
The inverse function is given in the form:
[tex]\[ f^{-1}(x) = a(x + 2) \][/tex]
To find the slope [tex]\( a \)[/tex] of the inverse function, let's first determine the actual form of the inverse function of [tex]\( f(x) \)[/tex].
### Finding the Inverse Function:
1. Start with the equation for [tex]\( f(x) \)[/tex], and let [tex]\( y = f(x) \)[/tex]:
[tex]\[ y = \frac{1}{3}x - 2 \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y + 2 = \frac{1}{3}x \][/tex]
[tex]\[ 3(y + 2) = x \][/tex]
[tex]\[ x = 3y + 6 \][/tex]
3. Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to express the inverse function:
[tex]\[ f^{-1}(x) = 3(x + 2) \][/tex]
### Comparing with the Given Form:
The inverse function is given as [tex]\( f^{-1}(x) = a(x + 2) \)[/tex]. By comparison:
[tex]\[ 3(x + 2) \quad \text{and} \quad a(x + 2) \][/tex]
We can see that:
[tex]\[ a = 3 \][/tex]
### Finding the x-intercept:
To find the x-intercept of the inverse function [tex]\( f^{-1}(x) \)[/tex], set the function equal to 0 and solve for [tex]\( x \)[/tex]:
[tex]\[ 0 = 3(x + 2) \][/tex]
[tex]\[ 0 = 3x + 6 \][/tex]
[tex]\[ 3x = -6 \][/tex]
[tex]\[ x = -2 \][/tex]
Therefore, the slope [tex]\( a \)[/tex] of the inverse function is [tex]\( 3 \)[/tex] and the x-intercept of the inverse function is at [tex]\( x = -2 \)[/tex].
The function is:
[tex]\[ f(x) = \frac{1}{3}x - 2 \][/tex]
The inverse function is given in the form:
[tex]\[ f^{-1}(x) = a(x + 2) \][/tex]
To find the slope [tex]\( a \)[/tex] of the inverse function, let's first determine the actual form of the inverse function of [tex]\( f(x) \)[/tex].
### Finding the Inverse Function:
1. Start with the equation for [tex]\( f(x) \)[/tex], and let [tex]\( y = f(x) \)[/tex]:
[tex]\[ y = \frac{1}{3}x - 2 \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y + 2 = \frac{1}{3}x \][/tex]
[tex]\[ 3(y + 2) = x \][/tex]
[tex]\[ x = 3y + 6 \][/tex]
3. Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to express the inverse function:
[tex]\[ f^{-1}(x) = 3(x + 2) \][/tex]
### Comparing with the Given Form:
The inverse function is given as [tex]\( f^{-1}(x) = a(x + 2) \)[/tex]. By comparison:
[tex]\[ 3(x + 2) \quad \text{and} \quad a(x + 2) \][/tex]
We can see that:
[tex]\[ a = 3 \][/tex]
### Finding the x-intercept:
To find the x-intercept of the inverse function [tex]\( f^{-1}(x) \)[/tex], set the function equal to 0 and solve for [tex]\( x \)[/tex]:
[tex]\[ 0 = 3(x + 2) \][/tex]
[tex]\[ 0 = 3x + 6 \][/tex]
[tex]\[ 3x = -6 \][/tex]
[tex]\[ x = -2 \][/tex]
Therefore, the slope [tex]\( a \)[/tex] of the inverse function is [tex]\( 3 \)[/tex] and the x-intercept of the inverse function is at [tex]\( x = -2 \)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.